2020
DOI: 10.1021/acsomega.9b03740
|View full text |Cite
|
Sign up to set email alerts
|

Facile One-Pot Solvothermal Synthesis of the RGO/MWCNT/Fe3O4 Hybrids for Microwave Absorption

Abstract: How to effectively regulate the electromagnetic parameters of magnetic composites to achieve better microwave absorption (MA) performances is still a serious challenge. Herein, we constructed nanocomposites composed of magnetic constituents and carbon materials to obtain high-efficiency electromagnetic wave absorbers. Self-assembled, multi-interfacial, and porous RGO/MWCNT/Fe3O4 hybrids (GMFs) were synthesized via in situ one-pot solvothermal method. The growth mechanism of the GMFs would be that the defects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…The D band around 1343 cm –1 is attributed to the presence of chaotic graphite structures caused by amorphous carbon and defects, which stems from the symmetric A 1g model of defective graphite. The G band near 1571 cm –1 is derived from the tangential in-plane tensile vibration of the C–C band, which is attributed to the E 2g graphite model. In addition, the intensity of the G-band is stronger than the intensity of the D-band, and the intensity ratio of the D-band and G-band ( I D / I G ) is used to evaluate the degree of modification or defect of the rGO . The Raman results confirmed that the prepared rGO-Fe 3 O 4 composites have a lower I D / I G ratio, exhibiting an ordered crystalline structure in the presence of fewer structural defects. The overall XRD patterns for reduced graphene oxide (rGO), pure Fe 3 O 4 NPs, and rGO-Fe 3 O 4 composites are shown in Figure e.…”
Section: Resultsmentioning
confidence: 73%
“…The D band around 1343 cm –1 is attributed to the presence of chaotic graphite structures caused by amorphous carbon and defects, which stems from the symmetric A 1g model of defective graphite. The G band near 1571 cm –1 is derived from the tangential in-plane tensile vibration of the C–C band, which is attributed to the E 2g graphite model. In addition, the intensity of the G-band is stronger than the intensity of the D-band, and the intensity ratio of the D-band and G-band ( I D / I G ) is used to evaluate the degree of modification or defect of the rGO . The Raman results confirmed that the prepared rGO-Fe 3 O 4 composites have a lower I D / I G ratio, exhibiting an ordered crystalline structure in the presence of fewer structural defects. The overall XRD patterns for reduced graphene oxide (rGO), pure Fe 3 O 4 NPs, and rGO-Fe 3 O 4 composites are shown in Figure e.…”
Section: Resultsmentioning
confidence: 73%
“…Zhou synthesized a new absorbing material of RGO/ MWCNT/Fe 3 O 4 hybrids (GMFs). [15] The GMFs exhibited the reflection loss (RL min ) value is À 61.29 dB. The above results show the incorporation of dielectric loss materials with magnetic loss materials would improve the absorption performance.…”
Section: Introductionmentioning
confidence: 69%
“…Dielectric loss and magnetic loss tangent are crucial parameters to determine the dominating loss mechanism in the microwave absorbing mechanism . As shown in Figure a, ε′ decreases gradually from 2 to 18 GHz, which may be caused by the frequency-dispersion phenomenon . Both ε′ and ε″ decrease from NFCR-500 to NFCR-700 with the carbothermal reduction temperature increase.…”
Section: Resultsmentioning
confidence: 99%